KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP MELALUI PEMBERIAN PERLAKUAN PEMBELAJARAN - Gugun Gunawan; Ulsan Fitriana; Kushendri Kushendri; Fatimah Fatimah; Chintya Zulvi Mustika; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This study aims to find out and examine the comparison of the results of tests of students' mathematical problem solving abilities in the comparison material. The type of research used was quasi-experimental (not randomized class) taken 2 classes namely class A and class B to study the ability to solve mathematical problems of students in one of the junior high schools in Kabupaten Bandung Barat. Class A is the class that gets the learning treatment and class B is the class that does not receive learning treatment before the problem solving ability test. The instrument used in this study was a test of mathematical problem solving abilities. The population in this study were class VII students and the samples in this study were classes VII-G and VII-H. Based on the results of the analysis of research data, the average value of class A is 79.84 and the average grade B value is 58.55. Problem solving analysis on indicator 1 can be said that students have been able to identify all known elements, asked questions and adequacy of elements, on indicator 2 students have been able to show strategies used to solve problems, on indicators of 3 students who have been able to do calculations and decision making. It can be concluded that the results of the test of problem solving ability of comparative material, the class given the treatment of learning is better than those not given the learning treatment